Meningkatkan Motivasi Belajar Siswa Melalui Bimbingan Belajar Jawara di Dukuh Dayakan, Ds. Wagir Lor, Kec. Ngebel - Ika Khofifaturrohmah; Maulida Agustina HW (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This community service aims to increase students' learning motivation through tutoring programs conducted by students of the Community Service Program (KPM) in Dukuh Dayakan, Wagir Lor Village, Ponorogo. The method used is Asset-Based Community Development (ABCD) which consists of five stages: Discover, Dream, Design, Define, and Destiny. The results show that students are more motivated in learning, better understand the subject matter, and demonstrate improvements in confidence and independent learning skills. Moreover, this program not only benefits the students but also provides valuable experiences for KPM participants in applying their academic knowledge to real community settings. The collaborative approach between students, tutors, and the community fosters sustainable educational development and creates a positive learning environment. This indicates that the implementation of the ABCD method in tutoring activities has the potential to be replicated in other communities facing similar challenges in improving students’ learning motivation.